2019
DOI: 10.3390/ijerph16224338
|View full text |Cite
|
Sign up to set email alerts
|

Walking Green: Developing an Evidence Base for Nature Prescriptions

Abstract: Although the health benefits of exercise and exposure to nature are well established, most evidence of their interaction comes from acute observations of single sessions of activity. However, documenting improved health outcomes requires ongoing interventions, measurement of multiple outcomes, and longitudinal analyses. We conducted a pilot study to guide the development of a protocol for future longitudinal studies that would assess multiple physiological and psychological outcomes. Herein, we report psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 97 publications
3
75
0
4
Order By: Relevance
“…Interestingly, participants in both conditions expressed that merely being outdoors was a positive experience. This may suggest an overall benefit of being outdoors, despite the environment, which is in line with previous research that has highlighted an overall vitalizing effect of outdoor experiences [25,26,50]. This research seems to suggest that being outdoors can per se be conducive to vitality, although, based on our qualitative findings, nature might add extra energizing effect, as observed for instance in Ryan et al [26].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, participants in both conditions expressed that merely being outdoors was a positive experience. This may suggest an overall benefit of being outdoors, despite the environment, which is in line with previous research that has highlighted an overall vitalizing effect of outdoor experiences [25,26,50]. This research seems to suggest that being outdoors can per se be conducive to vitality, although, based on our qualitative findings, nature might add extra energizing effect, as observed for instance in Ryan et al [26].…”
Section: Discussionsupporting
confidence: 91%
“…In a study investigating forest bathing, or shinrin-yoku, researchers found that time spent in forests was associated with a reduction in reported feelings of hostility, depression, and anxiety among adults with acute and chronic stress [ 24 ]. Another study examining walking in different environments observed the largest and most consistent improvements in psychological states associated with forest walks [ 25 ]. Forest bathing may play an important role in health promotion and disease prevention.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have measured baseline indicators of time in nature to conclude that absence of nature contact is the population norm, with the consequence of "nature deprivation" [85] as permanent removal of nature contact being vulnerability to a range of negative health outcomes. Shared concern for a phenomenon described as the "rarity of direct experience in nature" [86] and characterized in the literature as nature deficiency [87] or nature impoverishment [23] has led to research on prescriptive nature re-engagement [88,89] and nature-based health treatment [90], especially among children. Still, conceptualization of nature deficit disorder [91] remains a descriptive and not diagnostic condition, with formal study elusive given research bounds, though a few exceptions exist [92].…”
Section: Background Literaturementioning
confidence: 99%